An analytical approach for solving a nodal formulation of two-dimensional fixed-source neutron transport problems with linearly anisotropic scattering - C.B. Picoloto, R. D. Da Cunha, R. C. Barros; Barichello, L.B. (Progress in Nuclear Energy, 2017)
n/a
n/a